Perceptions of social studies teachers about the role of strategic intelligence in supporting decision-making in pre-university education institutions and its impact on sustainable competitiveness - Al-Na'aimi, Muna Rashid (Journal of Educational and Psychological Sciences, 2023)
The current study reveals the perceptions of social studies teachers about the role of strategic intelligence in supporting decision-making in pre-university education institutions and its impact on sustainable competitiveness (17) A male and female teacher from North Al Batinah Governorate in the Sultanate of Oman, and the results of the study concluded that social studies teachers support “the school encourages its employees to work within the same team” more to support decision-making and develop sustainable competitiveness, while they support that “the school defines its goals precisely over the long term. far less impact on sustainable competitiveness. The researcher recommends the importance of extrapolating pre-university education institutions to global developments and diagnosing long-term opportunities to enhance their competitiveness, and the need to work with the perspective of strategic intelligence and its dimensions in future through the preparation of training programs and the use of experts specialized in strategic intelligence, decision-making and ways to employ its sustainable skills.
Keywords: Strategic intelligence; decision-making; pre-university education institutions; sustainable competitiveness